Outcomes of high-dose levofloxacin therapy remain bound to the levofloxacin minimum inhibitory concentration in complicated urinary tract infections. Issue 1 (December 2016) - Armstrong, Eliana; Mikulca, Janelle; Cloutier, Daniel; Bliss, Caleb; Steenbergen, Judith
Abstract Background Fluoroquinolones are a guideline-recommended therapy for complicated urinary tract infections, including pyelonephritis. Elevated drug concentrations of fluoroquinolones in the urine and therapy with high-dose levofloxacin are believed to overcome resistance and effectively treat infections caused by resistant bacteria. The ASPECT-cUTI phase 3 clinical trial (ClinicalTrials.gov, NCT01345929 andNCT01345955, both registered April 28, 2011) provided an opportunity to test this hypothesis by examining the clinical and microbiological outcomes of high-dose levofloxacin treatment by levofloxacin minimum inhibitory concentration. Methods Patients were randomly assigned 1:1 to ceftolozane/tazobactam (1.5 g intravenous every 8 h) or levofloxacin (750 mg intravenous once daily) for 7 days of therapy. The ASPECT-cUTI study provided data on 370 patients with at least one isolate of Enterobacteriaceae at baseline who were treated with levofloxacin. Outcomes were assessed at the test-of-cure (5–9 days after treatment) and late follow-up (21–42 days after treatment) visits in the microbiologically evaluable population (N  = 327). Results Test-of-cure clinical cure rates above 90% were observed at minimum inhibitory concentrations ≤4 μg/mL. Microbiological eradication rates were consistently >90% at levofloxacin minimum inhibitory concentrations ≤0.06 μg/mL. Lack of eradication of causative pathogens at the test-of-cure visit increased the likelihood of relapse by the late follow-up visit. Conclusions Results from this study do not support levofloxacin therapy for complicated urinary tract infections caused by organisms with levofloxacin minimum inhibitory concentrations ≥4 μg/mL. Trial registration ClinicalTrials.gov, NCT01345929 andNCT01345955